Cover crops affect the partial nitrogen balance in a maize-forage cropping system - Rocha, Kassiano F.; de Souza, Murilo; Almeida, Danilo S.; Chadwick, David R.; Jones, Davey L.; Mooney, Sacha J.; Rosolem, Ciro A. (Geoderma, 2020)
•Part of the N applied to crops is lost to the environment.•Cover crops are one tool to improve N use efficiency, avoiding N loss.•In a N poor environment, cover crops can help prevent N leaching.•N loss is not modified by different cover crops grown in rotation with maize.•N export in maize grains controls the negative N balance in the system. Part of the nitrogen (N) fertilizer applied to crops is lost to the environment, contributing to global warming, eutrophication, and groundwater contamination. However, low N supply stimulates soil organic N turnover and carbon (C) loss, since the soil N/C ratio in soil is quasi-constant, ultimately resulting in land degradation. Grasses such as ruzigrass (Urochloa ruziziensis) grown as winter pasture or a cover crop in rotation with maize (Zea mays) can reduce N leaching, however, this may induce N deficiency and depress yields in the subsequent maize crop. Despite the potential to decrease N loss, this rotation may negatively affect the overall N balance of the cropping system. However, this remains poorly quantified. To test this hypothesis, maize, fertilized with zero to 210 kg N ha−1, was grown after ruzigrass, palisade grass (Urochloa brizanta) and Guinea grass (Pannicum maximum), and the N inputs, outputs and partial N balance determined. Despite the intrinsically poor soil quality associated with the tropical Ultisol, maize grown after the grasses was efficient in acquiring N, resulting in a negative N balance even when 210 kg ha−1 of N was applied after Guinea grass. Losses by leaching, N2O emission and NH3 volatilization did not exceed 13.8 kg ha−1 irrespective of the grass type. Despite a similar N loss among grasses, Guinea grass resulted in a higher N export in the maize grain due to a higher yield, resulting in a more negative N balance. Soil N depletion can lead to C loss, which can result in land degradation.